ANALISIS KATA GANTI BAHASA MAYBRAT DIALEK MAYMARU KAMPUNG SUWIAM DISTRIK AYAMARU UTARA TIMUR KABUPATEN MAYBRAT - Irwan Soulisa; Welmince Jitmau (LPPM Politeknik Saint Paul Sorong, 2022)
The formulation of the problem of moral values ​​is contained in the analysis of pronouns in the Maybrat dialect, the Maymaru dialect, Suwiam village, North East Ayamaru district, Maybrat district? The purpose of the study was to find out the use of Maybrat pronouns in the Maymaru dialect of Suwiam Village, North East Ayamaru District, Maybrat Regency. This research is in the form of a qualitative descriptive. The method used is descriptive method. The data source is Maybrat language, Maymaru dialect, Maybrat district and from the internet. The data collection technique used the method of observing (observation) (2) the speaking method (interview) and (3) the introspection method. Data analysis techniques used include matching and distributor methods. The data validity technique in this research is method triangulation technique, theory triangulation, data source triangulation technique. The conclusion is that there are 6 pronouns in the Maybrat language with the Maymaru dialect, namely (1) first, second, third person pronouns (2) possessive pronouns, (3) pen pronouns, (4) connecting pronouns, (5) clue pronouns. , (6) indefinite pronoun.